Early‐life foraging: Behavioral responses of newly fledged albatrosses to environmental conditions. Issue 17 (26th July 2017) - de Grissac, Sophie; Bartumeus, Frederic; Cox, Sam L.; Weimerskirch, Henri
Abstract: In order to survive and later recruit into a population, juvenile animals need to acquire resources through the use of innate and/or learnt behaviors in an environment new to them. For far‐ranging marine species, such as the wandering albatross Diomedea exulans, this is particularly challenging as individuals need to be able to rapidly adapt and optimize their movement strategies in response to the highly dynamic and heterogeneous nature of their open‐ocean pelagic habitats. Critical to this is the development and flexibility of dispersal and exploratory behaviors. Here, we examine the movements of eight juvenile wandering albatrosses, tracked using GPS/Argos satellite transmitters for eight months following fledging, and compare these to the trajectories of 17 adults to assess differences and similarities in behavioral strategies through time. Behavioral clustering algorithms (Expectation Maximization binary Clustering) were combined with multinomial regression analyses to investigate changes in behavioral mode probabilities over time, and how these may be influenced by variations in day duration and in biophysical oceanographic conditions. We found that juveniles appeared to quickly acquire the same large‐scale behavioral strategies as those employed by adults, although generally more time was spent resting at night. Moreover, individuals were able to detect and exploit specific oceanographic features in a manner similar to that observed in adults. Together, the results of this study suggest that while shortly after fledging juvenile wandering albatrosses are able to employ similar foraging strategies to those observed in adults, additional skills need to be acquired during the immature period before the efficiency of these behaviors matches that of adults. Abstract : We examined how the behaviour of juvenile seabirds changed during the first months after fledging and its relationship with environmental conditions. Juvenile's behavioural strategy was then compared to that of adults. We found that they are able to adjust their search strategy to the habitat visited. They can detect specific oceanographic features and behave accordingly, almost similarly to adults.